Clause as Exchange and Representation Analyses in Jokowi’s False Diploma Scandal News Article: An SFL Approach - Muhammad Aziz Fitratama (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study examines how language shapes public opinion in news articles about President Joko Widodo's alleged fraudulent diploma. Using the Systemic Functional Linguistics (SFL) framework, the study focuses on the clause as exchange (Mood system) and clause as representation (Transitivity system) to investigate the interpersonal and ideational meanings encoded in the text. The research uses a qualitative descriptive method based on Halliday and Matthiessen's (2014) theory to examine chosen online news stories from national media sources that cover the diploma issue. Each clause is evaluated to determine the mood types, process types, participants, and conditions. The findings suggest a predominance of declarative Mood types, which are employed to explain facts and assert claims, indicating how authors establish authority and persuade readers. Material and relational processes are the most commonly used, emphasizing acts and assigning attributes to Jokowi and institutional actors. This study concludes that news articles covering politically sensitive matters such as Jokowi's diploma are not objective, but are affected by linguistic tactics that serve ideological purposes. Using SFL analysis, the study demonstrates how media language produces social reality, contributing to critical media literacy and discourse awareness in sociopolitical contexts.